Association of MMP-8 rs2012390 and rs11225394 polymorphisms with osteonecrosis of the femoral head risks: Evidence from a meta-analysis - Jiang, Liangbin (Medicine (Baltimore), 2018)
BACKGROUND: The association of MMP-8 rs2012390 and rs11225394 polymorphisms with osteonecrosis of the femoral head (ONFH) risks was investigated in several studies with conflicting results. We performed the meta-analysis to evaluate the association between them. METHODS: Potentially relevant literatures were searched from the electronic databases of PubMed, Web of Science, and Cochrane Library. All databases were searched up to May 6, 2018. The strength of associations of the MMP-8 rs2012390 and rs11225394 polymorphisms with ONFH risk was assessed by crude odds ratios (ORs) with their 95% confidence intervals (CIs) under different genetic models. RESULTS: A total of 1469 cases diagnosed with ONFH and 1211 healthy controls were included in the current meta-analysis. A remarkable association between rs11225394 in the MMP-8 gene and an increased risk of ONFH was found (allele model: OR = 1.33, 95% CI = 1.09–1.61, P = .005; heterozygote model: OR = 1.39, 95% CI = 1.13–1.71, P = .002; dominant model: OR = 1.40, 95% CI = 1.14–1.73, P = .002, respectively). Meanwhile, a significant association between MMP-8 rs2012390 and the decreased risk of ONFH was found in heterozygote model (OR = 0.63, 95% CI = 0.51–0.77, P < .00001). CONCLUSION: The meta-analysis results showed a remarkable association between rs11225394 in MMP-8 gene and an increased risk of ONFH and a significant association between MMP-8 rs2012390 and the decreased risk of ONFH.